(untitled) (Indian Journal of Arid Horticulture, 2025)
The stem-end rot of Kinnow (Citrus deliciosa Ten.) caused by Botryodiplodia theobromae is a major limiting factor in storage life of Kinnow fruits, responsible solely for 20 per cent of the total fruit loss occurred every year due to post- harvest rotting in Sriganganagar belt of Rajasthan. Nine fungicides were tested against the B. theobromue as well as incited rot. Prochloraz and carbendazim proved most effective against the pathogen, inhibited cent per cent mycelial growth and provided complete protection from the rot incidence in both pre- and post-inoculation treatments at 1000 ppm concentration. The mancozeb in association with carbendazim (saaf) and mancozeb alone were the next in order of efficacy where, 100 and 91.24 per cent growth inhibition, respectively was observed. These fungicides potencially reduced the incidence to the extent of 87.84 and 81.41 per cent, respectively as compared to control when applied as pre-inoculation treatment at 1000 ppm concentration. The fruit rot incidence correlated positively with incubation period, where the incidence at 8th day, after inoculation (DA!) was significantly higher than incidence occurred at 4th DAI.